Allowing time for 8+ hours of sleep: identification and validation of important beliefs using the reasoned action approach - Tagler, Michael J. (Frontiers in Psychology, 2024)
Introduction The present studies advance research using the Reasoned Action Approach to understand sleep behavior. Identification of the modal salient beliefs that individuals hold regarding their sleep habits is necessary to understand the attitudes, perceived normative pressure, and perceived behavioral control (PBC) that individuals hold. Methods Belief elicitation (Study 1) and follow-up validation (Study 2) studies of undergraduates at a Midwestern USA university were conducted to identify readily accessible and important beliefs regarding allowing time for 8+ hours of sleep each night. Results Important attitude relevant beliefs included positive effects on mood, thinking, health, and productivity. Important normative beliefs were perceived injunctive pressure from family, health professionals, and significant others. Because of the strong influence of PBC on intentions/behavior, most important were control beliefs about the need for good time management. Discussion The present studies increased our understanding why many individuals do not allow time to obtain adequate sleep. Identification of the beliefs that distinguish between those who intend to allow time for adequate sleep and those who do not is a necessary step toward the design of effective interventions to improve sleep duration. The results indicate that a focus on increasing time management skills and PBC may be an effective approach for sleep interventions.